2019
DOI: 10.1016/j.snb.2019.01.102
|View full text |Cite
|
Sign up to set email alerts
|

Application of 4-amino-N-adamantylphthalimide solvatochromic dye for fluorescence microscopy in selective visualization of lipid droplets and mitochondria

Abstract: 4-Amino-N-adamantylphthalimide (1) is a dye with moderate absorptivity (in CH3CN ε363 = 4200 M-1 cm-1) and high quantum yield of fluorescence (ΦF = 0.15-0.80) that exhibits fluorosolvatochromic properties. The dye can be excited at 405 nm and the position of fluorescence maximum and the Stokes shift are well correlated with the ET(30) parameter. The excitation in the near-visible part of the spectrum and low cytotoxicity allow use of the dye in live cell microscopy. Due to its amphiphilic character, the dye st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Rather, the compounds induce a strong cytotoxic effect. Still, as we previously demonstrated that compound 3 enters the membranes of mitochondria, [ 23 ] we assume that compounds 3 and 5 could similarly localize to mitochondrial membranes and probably induce mitochondrial dysfunction. It is worth noting that the interaction of some widely used drugs with mitochondria that have been associated with mitochondrial dysfunction appears to follow complex mechanisms, including membrane disruption.…”
Section: Resultsmentioning
confidence: 63%
“…Rather, the compounds induce a strong cytotoxic effect. Still, as we previously demonstrated that compound 3 enters the membranes of mitochondria, [ 23 ] we assume that compounds 3 and 5 could similarly localize to mitochondrial membranes and probably induce mitochondrial dysfunction. It is worth noting that the interaction of some widely used drugs with mitochondria that have been associated with mitochondrial dysfunction appears to follow complex mechanisms, including membrane disruption.…”
Section: Resultsmentioning
confidence: 63%
“…Phthalimide derivatives 1-6 were prepared according to procedures published in literature precedent. 56,57 The synthesis involves condensation of 3-aminoadamantane-1-carboxylic acid with various 4-substituted phthalic anhydrides, and some subsequent transformations such as cleavage of the OMe ether by BBr 3 , or reduction of the nitro group to amino. Preparative irradiations of 1-6 were conducted in CH 3 CN-H 2 O, or acetone-H 2 O mixtures (3:1 -v/v), in the presence of potassium carbonate to deprotonate the carboxylic functional group at the adamantane moiety.…”
Section: Synthesis and Preparative Photochemistrymentioning
confidence: 99%
“…Although photochemical transformations of phthalimides are very useful in organic synthesis, not much is known about the photochemistry of their substituted derivatives, [47][48][49] with a notable exception of 4-aminophthalimide derivatives, which are known for their photochemical stability and high fluorescence quantum yields. [50][51][52][53][54][55][56] Photochemical reactivity and photophysical properties for 1-6 were investigated by preparative irradiations, steady-state and time-resolved fluorescence spectroscopy and laser flash photolysis (LFP). The photochemical experiments allowed for a complete elucidation of plausible pathways, particularly PET, which were put in connection with electrochemical properties of the molecules determined by cyclic voltammetry and pK a values measured by UV-Vis and fluorescence pH titrations.…”
Section: Introductionmentioning
confidence: 99%
“…Ключевые слова: экспериментальные спектры люминесценции; поглощение; флуоресценция; стоксовы сдвиги; 4-аминофталимиды; временно-зависимая теория функционала плотности; модель поляризуемого континуума 4-Aminophthalimide 1 combines electron-donating amino group conjugated with the phthalimide moiety; this determines its distinct fluorescent properties (Stokes shifts > 100 nm) [1]. The derivatives of 1 continuously attract great attention because of biological applications [2], particularly as fluorescent markers [3] and environment-sensitive probes [4]. The fluorescence spectra of 1 not only strongly depend on the substituents [2,5], but are remarkably solvent-sensitive due to the intramolecular charge transfer nature of the emitting state.…”
mentioning
confidence: 99%
“…The derivatives of 1 continuously attract great attention because of biological applications [2], particularly as fluorescent markers [3] and environment-sensitive probes [4]. The fluorescence spectra of 1 not only strongly depend on the substituents [2,5], but are remarkably solvent-sensitive due to the intramolecular charge transfer nature of the emitting state. It has been found that bathochromic shifts of the emission spectra of 1 in protic solvents are much greater than those observed in aprotic ones: the emission maximum shifts from 430 nm in toluene to 550 nm in water [6 -7].…”
mentioning
confidence: 99%